The Role of Technology in English Language Learning in Online Classes at Tertiary Level (Journal of Social Sciences Review, 2023)
The primary objective of the study is to investigate the relationship between the TAM (Technology Acceptance Model) factors and online applications usage for language learning. Additionally, the influence of gender and prior technology use practice have been investigated by the study. In order to comprehend the user's responses to the technology used for language learning, this study used a quantitative approach and a TAM questionnaire to collect data. The study's participants are one hundred undergraduate English as a second language students who took online courses during the COVID-19 pandemic. Students' behavioral intentions, attitudes, and app use were found to be significantly positively correlated in the research results. Besides, a positive affiliation exists between the factors; seen usability, perceived use, genuine use, and behavior. In addition, the experience has been found to be positively correlated with TAM factors, whereas gender does not appear to be associated with any TAM factors. The study suggested using technology in the classroom to make learning a second language more fun for students.
Keywords: Language Learning; Attitudes; Online Applications; TAM; Gender